ELECTRONIC PROBLEM-BASED LEARNING WITH COLLASSION LEARNING - Dwinita Arwidiyarti,; Khaerudin,; Basuki Wibawa, (Journal of Islamic, Social, Economics and Development, 2022)
The goal of this study is to evaluate the effectiveness of the e-PBL with CollassionLearning model in the Information System Analysis and Design course. Collassion Learning isa form of blended learning that places a premium on collaborative learning and studentdiscussion. Students can use the Collassion Learning App to collaborate and discuss in smallgroups both inside and outside the classroom. Without regard for space or time constraints,lecturers can monitor and provide feedback directly. This study employs the R&D method. Thet-test yields a value of -4.024 with a significance level of 0.001. 3.55181 is the value of the ttablewith N=20. Because t-count is less than t-table, it is plausible to conclude that significantvariations in learning outcomes exist before to and following the adoption of the e-PBL-basedInformation System Analysis and Design learning model with Collassion Learning. The e-PBLlearning model combined with Collassion Learning is suggested as a way to improve theeffectiveness of the Information System Analysis and Design course.